Musykilat Ta’lim Al-Lughah Arabiyah Fii Madrasah Tarbiyah ‎Islamiyah Bayur Agam - Quratul Aini (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
This research problem is the problem of learning Arabic at MTI Bayur. ‎Arabic language learning is divided into two parts: linguistic and non-linguistic. ‎The problem of teaching Arabic that the author refers to is a non-linguistic ‎problem that must be solved. Non-linguistic problems found in MTI Bayur are ‎teacher competence, textbooks and infrastructure. So this article reveals the ‎learning problems that exist in MTI Bayur. The formulation of the problem in ‎this study is "What are the problems of teaching Arabic at MTI Bayur?". This ‎study aims to determine the competence of Arabic teachers and textbooks used ‎in Arabic language teaching and tools to assist Arabic language teaching at ‎MTI Bayur Agam. As for the research methodology used, it is qualitative ‎descriptive. Data collection techniques by observation, interviews, ‎documentation and questionnaires. The results of research in terms of Arabic ‎teacher competence are: Pedagogical Competence, that Arabic teachers are able ‎to master the subject matter but are less able to manage classes and use media. ‎Professional Competence, that Arabic teachers do not follow professional ‎development. Social Competence: That Arabic teachers are good at ‎communicating with students and other teachers. The competence of the ‎Arabic teacher's personality is good. Textbooks used in MTI Bayur and ‎infrastructure are also inadequate‎